Writing Old Age and Impairments in Late Medieval England - Rogers, Will (Borderlines Ser., 2021)
A ground-breaking study of old age impairments in Middle English literature and their function as prosthetic additions, which draw attention both to the debility of old age and its ability to complete and drive narrative.